Zalo Tank Mixtures for Early Postemergence Herbicide Efficacy in Corn - Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2024)
This study investigated Zalo herbicide with tank mix partners for season-long weed control in corn. All herbicide evaluated provided greater than 90% weed control early in the season, and Russian-thistle and buffalobur control remained high throughout the year. The best late-season puncturevine control was provided by Zalo plus Hornet; however, this treatment along with Liberty alone provided the least green foxtail control. Late season Palmer amaranth control declined to less than 90% with all treatments. Kochia control declined to less than 90% with Liberty, Zalo alone, Zalo plus S-metolachlor, and Zalo plus S-metolachlor and Hornet.
Keywords: herbicide antagonism